Merawat Keberagaman Melalui Pendidikan Multikultural di Tengah Dinamika Sosial Peserta Didik - Resti Yulastri; Alzahra Fita Salsabella; Hana Mufidah; Ira Mutia Agustina; Nadia Nabila (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2026)
This study aims to explore the role of multicultural education in promoting diversity among students within the school social environment and to examine strategies for strengthening tolerance and religious moderation in educational settings. The research employed a qualitative approach based on library research. Data were collected from various academic sources, including scholarly books, journal articles, and previous studies relevant to multicultural education, religious moderation, and school social dynamics. The analysis was conducted through several stages, including identifying, evaluating, and analyzing relevant literature, followed by data interpretation and synthesis. The findings indicate that multicultural education plays a crucial role in fostering tolerant, inclusive, and respectful attitudes among students from diverse cultural, religious, and social backgrounds. The integration of multicultural values through classroom instruction, school culture, teacher role modeling, and extracurricular activities contributes to the creation of a harmonious and inclusive learning environment. Furthermore, the incorporation of religious moderation values in education helps students avoid intolerance, discrimination, and radicalism while promoting social solidarity and empathy. The study suggests that schools should consistently integrate multicultural and religious moderation values into their educational practices to support the development of a more inclusive and cohesive society.